Impact Assessment of Project: Provision of Laptops to the Students of Public Sector Universities of Punjab (Pakistan) - Sajjad Mubin; Ekaterina Gavrishyk; Ghazanfar Mubeen (National University of Modern Languages (NUML), Islamabad, 2021)
Government of the Punjab (GOP) initiated a development project through which two hundred thousand (200,000) laptops were provided to meritorious students in two phases of the project along with free of cost on campus access to internet facility to cope with the challenges of the digitization brought about by the spread of Information and Communication Technology. The rationale behind the project was enhance the IT skills of students and to help students overcome the obstacles in the way of learning and professional growth in the modern times. It was envisaged that the laptops will improve the IT skills along with improvement in grades and outcomes of students'. At completion, the project was evaluated for assessment of outcomes and impact of the project on the beneficiaries. Moreover, the qualitative aspect of scheme was also analyzed, in terms of quality of laptops, warranty support, quality of internet connectivity, laptop distribution on merit and etc. Questionnaire was developed covering all the aspects of the project. Data was collected online from 3600 sampled students through Google form on a broad based methodology. Based on the data analysis, positive outcomes were observed almost in almost all quantitative and qualitative indicators defined for this evaluation. Detailed conclusions and recommendations are given in the last section of the paper.